A Novel Factor Essential for Unconventional Secretion of Chitinase Cts1 - Reindl, Michèle; Stock, Janpeter; Hussnaetter, Kai P.; Genc, Aycin; Brachmann, Andreas; Schipper, Kerstin (Frontiers in Microbiology, 2020)
Subcellular targeting of proteins is essential to orchestrate cytokinesis in eukaryotic cells. During cell division of Ustilago maydis, for example, chitinases must be specifically targeted to the fragmentation zone at the site of cell division to degrade remnant chitin and thus separate mother and daughter cells. Chitinase Cts1 is exported to this location via an unconventional secretion pathway putatively operating in a lock-type manner. The underlying mechanism is largely unexplored. Here, we applied a forward genetic screen based on UV mutagenesis to identify components essential for Cts1 export. The screen revealed a novel factor termed Jps1 lacking known protein domains. Deletion of the corresponding gene confirmed its essential role for Cts1 secretion. Localization studies demonstrated that Jps1 colocalizes with Cts1 in the fragmentation zone of dividing yeast cells. While loss of Jps1 leads to exclusion of Cts1 from the fragmentation zone and strongly reduced unconventional secretion, deletion of the chitinase does not disturb Jps1 localization. Yeast-two hybrid experiments indicate that the two proteins might interact. In essence, we identified a novel component of unconventional secretion that functions in the fragmentation zone to enable export of Cts1. We hypothesize that Jps1 acts as an anchoring factor for Cts1.